Penerapan Metode Supply Chain Management Sistem Informasi Restoran - Leony Hoki; Suriaty Suriaty (Universitas Budi Darma, 2022)
One of the trending business opportunities and much in demand by the public is in the culinary business. Many people are competing to open a restaurant because food is a basic need that must be met by humans, so opening a restaurant will certainly provide many benefits for restaurant owners. In a restaurant business process, of course, it involves many roles such as the role of a waiter, the role of a chef, the internal role of the raw material stock section, and so on are interrelated and must be synchronized. However, in practice, restaurants still use conventional methods that are inefficient, effective, and structured. Some restaurants in the city of Medan only use conventional records both in ordering and recording raw material stocks so that errors often occur due to the inaccurate calculation process. In addition, the business processes in a restaurant are still not well structured between each working part so that ordering errors often occur. Therefore, research will be conducted to build a restaurant information system using the Supply Chain Management method. The results showed that the application of the Supply Chain Management method to the restaurant information system that was built was proven to be able to integrate all parts of the restaurant business properly so as to prevent errors from occurring by every party working in the restaurant.